The Impact of Socio-Demographic Characteristics on Quality of Life Among Dental Students in Iraq - Jenan Othmaan Almaas1 , Ban Sahib Diab2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The purpose of this study was to assess the impact of socio-demographic factors on quality of life amongdental students in three governorates in Iraq.This observational study included 1364 dental students aged 18–22 years from three governorates. Informationon socio-demographic and quality of life was obtained from a structured, self-administered questionnairefrom the students who were willing to participate in the study. The data was collected, summarized andstatistically analyzed. The percentage of fair scores for the four domains was higher among dental students.Socio-demographic characteristics (age, gender and smoking status) were closely associated with quality oflife except the area of residence showed no statistical significant differences with quality of life.The socio-demographic characteristic had some effect on quality of life of dental student